Slender Rails, Big Risk: The Kansas Central Railway, 1871-1935. - Wheeler, Jessica (Kansas State University, The Chapman Center for Rural Studies, 2013)
This study examines the role of the Kansas Central Railway in promoting small towns in northeast Kansas. Although ultimately failing in its charter, the KCR was critically important for tiny settlements. Research is based on legal sources, railway records, focused articles and books about narrow-gauge railroads.
Jessica Wheeler, “Slender Rails, Big Risk: The Kansas Central Railway, 1871-1935.,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/241.
Keywords: Atchison Topeka & Santa Fe; Denver; Kansas Pacific Railroad; Onaga; Vermillion River; The Leavenworth Times